(untitled) (South East Asia Journal of Public Health, 2013)
This was a descriptive type of cross-sectional study conducted in October, 2010, in three villages of Shahjadpur Upazila of Sirajganj district in Bangladesh. Among the rural households, those who visited medical practitioners in the last three months, were included in the study. The present study aimed to examine the pattern of prescriptions available at rural households of Bangladesh, to analyze the prescriptions whether diagnoses and/or lifestyles advice were mentioned, and to find out number of drugs and antibiotics (including their dose and duration of use) prescribed. During last three months, 68% respondents had attended a doctor’s chamber; however, prescriptions were available for 57% of the respondents. More than three quarters of the prescriptions (77.6%) included 3-5 medicines, and antibiotics were prescribed to 194 (61%) respondents which constituted 21.4% of the total number of drugs prescribed. The average number of drugs and antibiotics prescribed per prescriptions was 3.8 and 1.3 respectively. Only about 23% of the respondents received antibiotics for 3-6 days, 30% for 2 days, and 46% for one day. Advice on lifestyles and diagnoses were mentioned only to 32% and 52% prescriptions respectively. The study also found that 22.6% of the prescriptions were made by unqualified doctors. Specific programs should be implemented to motivate and train medical students, practitioners and allied health professionals to provide rational prescriptions to the consumers in regards to the number of drugs as well as clarity of instructions given in the prescriptions. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13207 South East Asia Journal of Public Health 2011:1:12-16